Oxidative metabolism in the cardiorespiratory system after an acute exposure to nickel-doped nanoparticles in mice. (December 2021) - Garcés, Mariana; Marchini, Timoteo; Cáceres, Lourdes; Calabró, Valeria; Mebert, Andrea M.; Tuttolomondo, María Victoria; Vico, Tamara; Vanasco, Virginia; Tesan, Fiorella; Salgueiro, Jimena; Zubillaga, Marcela; Desimone, Martín F.; et al.
Graphical abstract: Highlights: Ni-NP alters lung O2 metabolism increasing ROS production by mitochondria and NOX. Ni-NP-increased ROS production leads to lung oxidative damage. Biodistribution studies showed no NP translocation into the circulatory system. Ni-NP exposure induces systemic oxidative stress along with PMN activation. Ni-NP alters heart O2 metabolism and increases mitochondrial H2 O2 production. Abstract: There is an increasing concern over the harmful effects that metallic nanoparticles (NP) may produce on human health. Due to their redox properties, nickel (Ni) and Ni-containing NP are particularly relevant. Hence, the aim of this study was to establish the toxicological mechanisms in the cardiorespiratory oxidative metabolism initiated by an acute exposure to Ni-doped-NP. Mice were intranasally instilled with silica NP containing Ni (II) (Ni-NP) (1 mg Ni (II)/kg body weight) or empty NP as control, and 1 h after exposure lung, plasma, and heart samples were obtained to assess the redox metabolism. Results showed that, NP were mainly retained in the lungs triggering a significantly increased tissue O2 consumption rate, leading to Ni-NP-increased reactive oxygen species production by NOX activity, and mitochondrial H2 O2 production rate. In addition, an oxidant redox status due to an altered antioxidant system showed by lung GSH/GSSG ratio decreased, and SOD activity increased, resulting in an increased phospholipid oxidation. Activation of circulating polymorphonuclear leukocytes, along with GSH/GSSG ratio decreased, and phospholipid oxidation were found in the Ni-NP-group plasma samples. Consequently, in distant organs such as heart, Ni-NP inhalation alters the tissue redox status. Our results showed that the O2 metabolism analysis is a critical area of study following Ni-NP inhalation. Therefore, this work provides novel data linking the redox metabolisms alterations elicited by exposure to Ni (II) adsorbed to NP and cardiorespiratory toxicity.